Identification of obstetric risks in COVID-19 times in a community health area, Ecuador - Cruz Marisol Zerna-Bravo; Alexandra María Alvarado-Álvarez; John Aníbal Herrera-Rivera; Francisco Mena-Martin (Revista Información Científica, 2022)
Introduction: risk factors associated with complications in the mother-child pair include: history of hypertensive disorders, adolescent pregnancy, drug use, unfavorable obstetric history with a background of miscarriages or abortions, sexually transmitted diseases and urinary tract infections.